170k views
1 vote
Can u pls give a clear explanation & word it out how u got the answer without using big words. Thank u

Can u pls give a clear explanation & word it out how u got the answer without-example-1

1 Answer

4 votes

A.

We can rewrite the squared in two ways.

The first way is to rewrite it as a multiplication, this is:


(y-6)^2=(y-6)(y-6)

The second way to rewrite the squared is by using the formula for this kind of product:


(y-6)^2=y^2+2(-6)(y)+(-6)^2

B.

Once again we can find the final result using each of the options given in part A, for the first option we have:


\begin{gathered} (y-6)^2=(y-6)(y-6) \\ =y^2-6y-6y+36 \\ =y^2-12y+36 \end{gathered}

For the second option we have:


\begin{gathered} (y-6)^2=y^2+2(-6)(y)+(-6)^2 \\ =y^2-12y+36 \end{gathered}

No matter which way we choose the answer for the squared is:


y^2-12y+36

User Tim Kennedy
by
5.1k points